The Effect of Catalysis on the Parameters of the Oxidation Reaction of Biodiesel. Issue 20 (11th July 2017) - Angilelli, Karina G.; Silva, Lívia R. C.; Chendynski, Letícia T.; da Silva, Paulo R. C.; Borsato, Dionisio
Abstract: Most commercial biodiesel is produced with homogeneous basic catalyst however, environmental and economically, the use of heterogeneous catalysis is potentially advantageous since they can be reused. This work aimed to evaluate the influence of homogeneous and heterogeneous catalysis on the oxidative stability of biodiesel by the determination of the kinetic and thermodynamic parameters of the oxidation reactions. The catalyst produced with a mixture of MgO and KOH (HetA) led to the production of biodiesel with the highest reaction yield, ester content and oxidative stability. Among the oxidation reaction parameters evaluated, the catalyst HetA and sodium methoxide showed the best results in terms of activation energy and activation enthalpy values. Both catalysts produced biodiesel with good results in terms of oxidative stability, though the HetA catalyst stands out for presenting the best results and underlines the advantages of employing a heterogeneous process. Abstract : Different catalysts produced with magnesium oxide and inorganic basis were applied to transesterificate a mixture of triacylglycerides. Biodiesel produced with catalyst HetA (MgO/KOH) does not require the addition of antioxidants and presented good properties and quality.